Effect of Giving Celecoxib on Uric Acid Level on Mice - Sara Surya (Borneo Journal of Pharmacy, 2018)
Celecoxib is a breakthrough for pain relievers under the trade name Celebrex®, which is a Non-Steroid Anti-Inflammatory drug with its activity as an analgesic, antipyretic and anti-inflammatory. The purpose of this study was to find out the effect of celecoxib on blood uric acid levels of female white mice was induced with fresh cow liver extract. Experimental animals were divided into five groups, namely the control group (-), the control group (+) and the three dose groups, respectively 0.26, 0.52 and 1.04 mg/20 g. Observations were made on 7, 14 and 21 days with the Enzymatic Photometric method. The results showed that administration of celecoxib suspension at a dose of 0.26, 0.52 and 1.04 mg/20 g did not affect blood uric acid levels when compared with controls (P> 0.05).